+0  
 
0
134
2
avatar

If ab = 15 and a^2 + b^2 = 40, then find (a + b)^4 - (a - b)^4.

 Dec 6, 2019
 #1
avatar
0

i got 4800

 Dec 6, 2019
 #2
avatar+111455 
+2

ab  = 15

 

a^2 + b^2  =   40

 

[ (a + b)^4  -  ( a - b)^4 ]   =

 

[ ( a + b)^2  + ( a - b)^2 ]  [ (a + b)^2 - ( a - b)^2  ]   =

 

[ a^2  + b^2 + a^2 + b^2 ] [ a^2 + b^2  - a^2 - b^2  + 4ab ]   =

 

[ 2 (a^2 + b^2) ]  [  4ab ]   =

 

[ 2 (40)  [ * [ 4(15) ]   =

 

[  80  ] * [ 60 ]  =

 

4800

 

 

 

cool cool cool

 Dec 6, 2019

21 Online Users

avatar
avatar